Aetiology of PCR negative suspected Crimean-Congo hemorrhagic fever cases in an endemic area. (3rd July 2016) - Tanyel, Esra; Sunbul, Mustafa; Fletcher, Tom E.; Leblebicioglu, Hakan
Abstract : Crimean–Congo hemorrhagic fever (CCHF) is a potentially fatal tick-borne viral infection that is widely distributed worldwide. The diagnosis is frequently missed due to the non-specific initial symptoms and the differential diagnosis included many infectious and non-infectious causes. This retrospective study describes the clinical features and final diagnoses of 116 suspect CCHF cases that were admitted to a tertiary CCHF center in Turkey, and were CCHF IgM and PCR negative.